Lipase mediated enzymatic kinetic resolution of phenylethyl halohydrins acetates: A case of study and rationalization - Fonseca, Thiago de Sousa; Vega, Kimberly Benedetti; da Silva, Marcos Reinaldo; de Oliveira, Maria da Conceição Ferreira; de Lemos, Telma Leda Gomes; Contente, Martina Letizia; Molinari, Francesco; Cespugli, Marco; Fortuna, Sara; Gardossi, Lucia; de Mattos, Marcos Carlos (Molecular Catalysis, 2020)
Racemic phenylethyl halohydrins acetates containing several groups attached to the aromatic ring were resolved via hydrolysis reaction in the presence of lipase B from Candida antarctica (Novozym® 435). In all cases, the kinetic resolution was highly selective (E > 200) leading to the corresponding (S)-β-halohydrin with ee > 99 %. However, the time required for an ideal 50 % conversion ranged from 15 min for 2,4-dichlorophenyl chlorohydrin acetate to 216 h for 2-chlorophenyl bromohydrin acetate. Six chlorohydrins and five bromohydrins were evaluated, the latter being less reactive. For the β-brominated substrates, steric hindrance on the aromatic ring played a crucial role, which was not observed for the β-chlorinated derivatives. To shed light on the different reaction rates, docking studies were carried out with all the substrates using MD simulations. The computational data obtained for the β-brominated substrates, based on the parameters analysed such as NAC (near attack conformation), distance between Ser-O and carbonyl-C and oxyanion site stabilization were in agreement with the experimental results. On the other hand, the data obtained for β-chlorinated substrates suggested that physical aspects such as high hydrophobicity or induced change in the conformation of the enzymatic active site are more relevant aspects when compared to steric hindrance effects.